Object-oriented Modelling Applied to Electricity Critical Infrastructures. (2015) - Bucovetchi, Olga; Simion, Cristina Petronela; Stanciu, Radu D.
Abstract: Given the current social and economic environment, critical infrastuctures and their protection are major debate topics. The present paper provides a methodological framework for risk assessement within the energy sector as critical infrastructure sector. The paper embedded the key concepts and key mechanisms of object-oriented modelling in order to build a risk multimodel that can be used as starting point in future protection strategies.